Osmotic demyelination syndrome: A pediatric case report and a systematic literature review - Y. Mouhcine; Z. Ezzoulali; H. Ouazzani; I. Chaouche; A. AKAMMAR; N. EL Bouardi; B. Alami; Y. Alaoui Lamrani; M. Maaroufi; M. Boubbou (Radiology Case Reports)
Osmotic Demyelination Syndrome (ODS) is a life-threatening neurologic disorder including two distinct types of demyelination: Central Pontine Myelinolysis (CPM) and Extrapontine Myelinolysis (EPM). While it's clear that the fast correction of low sodium levels is a key precipitating factor, the underlying pathophysiological mechanisms that cause ODS are still being explored. The present paper describes a case of an eleven-year-old male patient diagnosed with ODS based on typical imaging findings. This case report sounds like it could be significant by providing a thorough overview of the pathological findings, clinical outcomes, and imaging findings associated with this condition, particularly in pediatric cases. It also demonstrates the crucial role of MRI in diagnosing this condition.